The Politeness Speech of Primary School Teacher in the Character Building of Learners - Duhita, Arinanda Alma; Zulaeha, Ida (Pascasarjana Universitas Negeri Semarang, 2018)
Politeness is a social phenomenon and a way to create good relationships between people. Teacher speech has an important role in the character building of learners so that teachers should use polite language. Through the politeness of speech teachers can form a positive character of learners. This study aims to analyze the realization of compliance and violation of the principle of politeness and language politeness strategies in the speech of elementary school teachers in the formation of learner characters in the classroom. The research approach used is theoretical approach and methodological approach. The theoretical approach used is the pragmatic approach, while the methodological approach used is descriptive qualitative. The data of this research were collected through the simak method consisting of the technique of independent libat cognate (SBLC), recording technique and recording technique. Data analysis method used is method of normative method and heuristic technique. The results of the analysis found the realization of compliance, used by elementary school teachers in shaping the character of learners in the classroom.